Revisão sistemática de morcegos do gênero Anoura Gray, 1838 (Chiroptera : Phyllostomidae) com ênfase nas formas com distribuição a leste dos Andes - Natividade, Beatriz Dybas da (2024)
Anoura Gray, 1838 is the most diverse genus of nectarivorous/pollenivorous bats in the subfamily Glossophaginae and has a wide distribution, ranging from Mexico to northern Argentina, except for Chile. More than half of the species currently recognized were described from the 1980s onwards, and most of its diversity has been associated with the Andes. Therefore, little information about the Anoura populations east of the Andes is available, and material from this region has seldom been used in taxonomy reviews of the genus. In this context, this dissertation aimed to conduct a systematic review of the genus Anoura, with an emphasis on the forms distributed east of the Andes, to (1) describe, analyze, and test morphological variations of the species within the genus Anoura; (2) investigate the genetic diversity of species in the genus Anoura, testing phylogenetic relationships based on mitochondrial markers; (3) study the species composition of the genus Anoura using morphological and molecular data using species delimitation tests, phylogenetic analyses, morphometric analyses, and comparative morphology of discrete characters; and (4) review the occurrences and identifications of Anoura species to elucidate the limits of their geographic distributions. Chapter 1 of the dissertation addresses objectives 1, 2, and 3, and chapters 2 and 3 address objective 4. For Chapter 1, discrete and continuous morphological characters of 1015 specimens of Anoura comprising the entire distribution of the genus were analyzed. Sequences from two mitochondrial markers (239 individuals for Cytochrome oxidase subunit I and 67 individuals for Cytochrome B) were also used for phylogenetic analyses and species delimitation tests. Through morphological character analyses, it was possible to discriminate 14 morphotypes, 11 corresponding to currently recognized species or subspecies and three previously unrecognized, which can be divided into three species complexes: "caudifer complex," "geoffroyi complex," and "cultrata complex”. Phylogenetic results indicate the existence of 11 lineages within the genus Anoura; it also suggests the elevation of some subspecies to species status, points to an undescribed species closely related to A. luismanuel and shows the existence of at least two other lineages within A. caudifer. New morphological characters for diagnosing all species of the genus except A. fistulata are described. Furthermore, morphological and molecular evidence suggests that A. c. brevirostrum and A. g. lasiopyga should be treated as full species. Chapter 2 reports new records of A. caudifer in the northeastern portion of South America, with new records for Bahia and the first record for the State of Ceará, extending the species' range by more than 600 km. The third and lastchapter discusses new distribution records of a poorly known species, Anoura cadenai, documented here for the first time for Venezuela, increasing to 173 the number of bat species in this country.